Routledge handbook of biodiversity and the law
1 online resource
Keywords: "This volume provides a reference textbook and comprehensive compilation of multifaceted perspectives on the legal issues arising from the conservation and exploitation of non-human biological resources. Contributors include leading academics, policy-makers and practitioners reviewing a range of socio-legal issues concerning the relationships between humankind and the natural world. The Routledge Handbook of Biodiversity and the Law includes chapter on fundamental and cutting-edge issues, including discussion of major legal instruments such as the Convention on Biological Diversity and the Nagoya Protocol. The book is divided into six distinct sections based around the major objectives which have emerged from legal frameworks concerned with protecting biodiversity. Following introductory chapters, the second part examines issues relating to conservation and sustainable use of biodiversity, with part three focussing on access and benefit-sharing. Part four discusses legal issues associated with the protection of traditional knowledge, cultural heritage and indigenous human rights. The final two sections focus on a selection of intellectual property issues connected to the commercial exploitation of biological resources, and analyse ethical issues, including viewpoints from economic, ethnobotanical, pharmaceutical and other scientific industry perspectives."--Provided by publisher.